1994
DOI: 10.1007/bf00191165
|View full text |Cite
|
Sign up to set email alerts
|

Influences of trospium chloride and oxybutynin on quantitative EEG in healthy volunteers

Abstract: Trospium chloride and oxybutynin are two antimuscarinergic agents used in the treatment of unstable bladder, urge incontinence, combined stress urge incontinence and detrusor hyperreflexia. The possibility that these two drugs produce changes in central nervous electrical activity was examined in an open, prospective, phase I study involving 12 volunteers. Quantitative evaluation of the multichannel electroencephalogram obtained from young healthy volunteers showed statistically significant decreases in alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 7 publications
(3 reference statements)
3
63
0
4
Order By: Relevance
“…Thus, the selectivity for the urinary bladder over the brain was relatively low for oxybutynin, suggesting a high feasibility of CNS side effects at pharmacological doses to treat OAB. This finding seems to be in a reasonable agreement with previous observations of oxybutynin shown by pharmacological (Sugiyama et al, 1999) and ex vivo receptor binding (Oki et al, 2001) studies in rats and also by clinical studies (Pietzko et al, 1994;Katz et al, 1998;Todorova et al, 2001;Ancelin et al, 2006). In fact, CNS side effect by oxybutynin occurred in patients with OAB and in older subjects receiving this drug (Scheife and Takeda, 2005;Kay et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the selectivity for the urinary bladder over the brain was relatively low for oxybutynin, suggesting a high feasibility of CNS side effects at pharmacological doses to treat OAB. This finding seems to be in a reasonable agreement with previous observations of oxybutynin shown by pharmacological (Sugiyama et al, 1999) and ex vivo receptor binding (Oki et al, 2001) studies in rats and also by clinical studies (Pietzko et al, 1994;Katz et al, 1998;Todorova et al, 2001;Ancelin et al, 2006). In fact, CNS side effect by oxybutynin occurred in patients with OAB and in older subjects receiving this drug (Scheife and Takeda, 2005;Kay et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…They found that oxybutynin significantly altered qEEG activity, whereas tolterodine and trospium induce only a slight effect on qEEG activity. Similar electrophysiological results in healthy males with oxybutynin have been shown by Pietzko et al (1994).…”
Section: Discussionsupporting
confidence: 84%
“…They found that oxybutynin significantly altered qEEG activity, whereas tolterodine and trospium induce only a slight effect on qEEG activity. Similar electrophysiological results in healthy males with oxybutynin have been shown by Pietzko et al [84]. …”
Section: Cardiovascular Safetysupporting
confidence: 77%
“…In 1994 Pietzko et al [22] used quantitative evaluation of the multichannel electroencephalogram (EEG) obtained from young healthy volunteers to study possible CNS adverse effects of oral oxybutynin, oral and intravenous trospium chloride, and no drugs. The biologic activity of these drugs was ascertained by simultaneous recording of the heart rate.…”
Section: Quantitative Topographic Electroencephalogram Studies For Pomentioning
confidence: 99%